Status of human cystic echinococcosis based on hospital records in Mazandaran Province: A first registry-based evidence - Tabaripour, Rabeeh; Sharifpour, Ali; Fakhar, Mahdi; Asadi, Samira; Esmaeili Reykandeh, Samira; Montazeri, Mahbobeh; Keighobadi, Masoud (Parasite epidemiology and control, 2023)
Human cystic echinococcosis, as an emerging neglected parasitic disease, is caused by tapeworms of the genus Echinococcus spp. Because of the medical and economic importance, this study aims to review the epidemiology and clinical features of hydatidosis in patients admitted to medical and surgical wards in three referral teaching hospitals over 15 years in Mazandaran Province, northern Iran. Data were collected from hospital records that were accessible via the hospital information system (HIS) between 2005 and 2019 (15 years).The demographic information (age, sex, living area, and occupation), dog contact, number of the cysts, types of organs involved, and history of disease recurrence were assessed. One hundred twenty-one patients with human cystic echinococcosis (CE) were involved in the study, from whom 58 patients (47.93%) were male and 63 (52.07%) were female. The majority of patients were rural residents (64.46%) and also housewife (28.10%). Based on the results, only about 16.53% of the patients had history of close contacts with dogs. The liver was the organ involved in the most cases of CE. There were statistically significant differences between residence, occupation, history of close contacts with dogs, type of organs involved, number of cysts and history of disease recurrence (P < 0.05). Our data provides valuable registry-based information about CE in an endemic region. The data highlights that most patients lived in rural areas and were housewives. Additionally, they had a low rate of disease recurrence but a high rate of close contact with dogs. Moreover, further monitoring on registry-based program and strengthening the HIS in the provincial hospitals in the studied area are required.